Pogląd chrześcijaństwa prawosławnego na religie świata - Rus, Remus (Poznańskie Studia Teologiczne, 2008)
The article presents the thought of Father Dumitru Staniloae ( t 1993), one of the most outstanding Romanian theologians of the 20th century, based on his book Poztia d-lui Lucian Blaga fata de Crestinism si Ortodoxie (The Attitude of Mr. Lucian Blaga toward Christianity and Orthodoxy) Sibiu, 1942. The author begins by expounding the general character of the universal religious phenomenon. Beyond the multiplicity of the forms and the ways in which religion is manifested there are certain common points. Fr. Staniloae distinguishes five such specific elements typical for religion: 1. a strong and steadfast faith in the truth of the things it professes; 2. the personal character of the ultimate reality; 3. there is a certain differentiation a believer makes between these ultimate realities with a clear and less clear personal character and nature - even though sometimes the divine reality is perceived in an extremely intimate relationship with nature, each religion preserves an awareness that the divine reality is something else than nature itself; 4. the belief in the self-revelation of the divine reality - it is a universal conviction with the believers of all religions that the Divinity revealed and reveals Itself and the data about It are not a figment of the human mind or imagination, a self-revelation of the human spirit; 5. a certain expectance, confidence and hope with which man ties himself up to the Divinity in as far as his destiny is concerned. The universal human consciousness expects and believes in man’s salvation from under the destructive power of nature or of certain evil forces. Expectation is a deep instinct of the human nature; faith is the mysterious power given to man at the same time with any religion. There is also a functional interpenetration of these elements. Faith without a personal God and without revelation cannot exist, nor without the presence of a purpose, as that of the salvation of existence. Their persistence reveals the existence of a personal relationship between God and man in the interest of his salvation, as well as man’s firm belief in the possibility of a personal salvation and in a special communion with God and, as a result, that there is also an interest on the part of God to save man. Faith and revelation are conveyed from generation to generation, but at the same time faith is largely produced by revelation, each man experiencing in a mysterious way the pressure of the ultimate reality upon his conscience. All kinds of theories have been conceived which see religion as originating from the divinization of the forces of nature, society, or a political leader etc. In reality however religious experience distinguishes the divine from all these phenomena, even though it may have the experience of the divine presence and of its power in connection with them. Religious experience is an awareness of the mysterious presence of the Divinity and as such any religious man knows the difference. In the case of the religious phenomenon we come across a minimal realization and participation of the ultimate reality pertaining essentially to the faith in the Divinity, to its revelation and to the hope in a personal salvation as a common minimal background of all religions, and as such of the Christian Faith. Fr Staniloae draws our attention to the fact that what counts in the relation among religions is not this minimal background but the contribution of each religion. In his attempt to draw a line between Christianity and the other religions, he asserts that everything the non-Christian religions possess in addition, as a surplus, is either a jungle of myths, or a resuscitation in different manners of the same minimal background which make up the universal religious conviction. Myth is a human invention bom of his endeavour to capture in image the basic fact of the Divinity and of Its revelation; hence a poetic and personalized expression of what is known through the general revelation, or a personalization of a power in nature or of a personal attribute. Christianity differs radically from these religions, because by the surplus it asserts, it testifies to an essential increase in the divine revelation. We have in Christianity the full revelation of the Divinity, as well as the manifestation of Its personal character as God has come as a man among men. Christianity is an entirely different religion in so far as the awareness of the nearness of the divine reality is concerned, as the only religion dominated by the awareness of an increase - to the last possible extent - in the divine revelation, without imposing a new element to the general definition of religion. Moreover, Christianity is not a religion of myths. This is due to the fact that God’s presence in the world, as a perceptible and active reality, renders futile all myths: when the divine reality is so close to us and so commanding, there is no longer any place for myths. At the same time there is no attitude which embraces all parts of the Universe with so much love and appreciation as does Christianity, because all are the work of the hands God and the object of His fatherly care.